Inducing Effect of Dihydroartemisinic Acid in the Biosynthesis of Artemisinins with Cultured Cells of Artemisia annua by Enhancing the Expression of Genes - Jianhua Zhu; Jiazeng Yang; Zihan Zeng; Wenjin Zhang; Liyan Song; Wei Wen; Rongmin Yu (The Scientific World Journal)
Artemisinin has been used in the production of “artemisinin combination therapies” for the treatment of malaria. Feeding of precursors has been proven to be one of the most effective methods to enhance artemisinin production in plant cultured cells. At the current paper, the biosynthesis of artemisinin (ART) and its four analogs from dihydroartemisinic acid (DHAA) in suspension-cultured cells of Artemisia annua were investigated. ARTs were detected by HPLC/GC-MS and isolated by various chromatography methods. The structures of four DHAA metabolites, namely, dihydro-epi-deoxyarteannuin B, arteannuin I, arteannuin K, and 3-β-hydroxy-dihydro-epi-deoxyarteannuin B, were elucidated by physicochemical and spectroscopic analyses. The correlation between gene expression and ART content was investigated. The results of RT-PCR showed that DHAA could up-regulate expression of amorpha-4,11-diene synthase gene (ADS), amorpha-4,11-diene C-12 oxidase gene (CYP71AV1), and farnesyl diphosphate synthase gene (FPS) (3.19-, 7.21-, and 2.04-fold higher than those of control group, resp.), which indicated that biosynthesis processes from DHAA to ART were enzyme-mediated.